Development of Contextual Teaching and Learning for Deaf Students - Muhammad Mufti Rakadia (Universitas Pendidikan Indonesia (UPI), 2022)
Development of CTL (Contextual teaching and learning) learning to understand learning material on energy sources for deaf children. This research method uses a qualitative descriptive method to gather information thoroughly. The subjects of this study were deaf students in grade 5 at an extraordinary elementary school in Bandung. The results of this study are the development of CTL learning for deaf students to understand learning material on energy sources for deaf children. Energy sources learning material adapted to the material being studied by students at this time. The results of this study are expected that the development of CTL learning for deaf students can benefit research subjects (students, teachers) from school institutions to improve the learning process.